Diagnostic outcome of fine needle aspiration cytology in 400 cases of head and neck masses in tertiary care center - Patel, Alpesh V.; Patel, Nehal R.; Vadher, Payal R.; Kakadia, Manali B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the study was to identify various lesions of neck swellings and to study their distributions according to age, sex and site and to find out distribution of malignant, inflammatory and infective lesions in neck swellings. Methods: The prospective study was conducted in the department of ENT, SCL General Hospital, NHL MMC, Saraspur, Ahmedabad from July 2014 to July 2016. All indoor and outdoor 400 patients of SCL hospital presenting with palpable head and neck swellings were referred to the cytology section at SCL hospital for FNAC and included in present study. Results: In our study out of 400 cases, lymph nodes constituted 276 cases with female preponderance. Among the inflammatory lesions, commonest lesion was tuberculosis which comprised of 147 cases followed by 64 cases of reactive lymphadenitis. In thyroid lesions the male: female ratio was 1:18, with maximum incidence in age group of 20-50 years. Total 95 cases were observed, out of which benign thyroid lesions (Bethesda grade II) were most common (92.63%). Salivary gland comprised of 11 cases, Out of 10 benign neoplastic lesions, 9 cases of pleomorphic adenoma and 1 cases of Warthin’s tumor were found. Conclusions: FNAC is a very simple and expeditious procedure which can be carried out without much problem. It reduces the necessities to perform excisions biopsy in many cases. Thus, FNAC can be recommended as a first line of investigation in the diagnosis of neck swellings and can be adopted as an outpatient procedure, thus reducing the cost and time of hospitalization.